Implementasi Kebijakan Pemerintah Tentang Pengurangan Penggunaan Kantong Plastik Pada Bisnis Retail Di Kabupaten Jepara - Murdyansyah Herman; Maliki Aji Prakoso; Bambang Agus Windusancono; Muhammad Daennie (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The purpose of this study was to investigate the execution of measures aimed at lowering the utilization of plastic bags within the retail market of Jepara Regency. The research employs a qualitative methodology, utilizing descriptive analytic techniques. The data-gathering process involved conducting an interview with the Head of Hygiene and Waste Management at the Jepara Regency Environment Office, who served as a key informant. In order to gather comprehensive data, interviews were conducted with both sellers and buyers at retail stores in Welahan, Mayong, and Pecangaan sub-districts. The findings of the study indicate that the implementation of the policy is facilitated by socializing activities, particularly in the context of communication and transmission. The Jepara regency government has conducted socialization efforts throughout nearly all marketplaces, demonstrating a clear and consistent approach. The implementation of policies involves the participation of human resources, namely the Environment Office, as the responsible entity. The necessary financial resources for policy implementation are also obtained through the Regional Revenue and Expenditure Budget. Regarding disposition, policy implementers have a preexisting commitment to effectively executing their responsibilities and exhibit a democratic mindset. In relation to bureaucratic organization, the execution of government policies is already directed by the established Standard Operating Procedure. However, there are still challenges for the government in terms of public response and low understanding of the dangers of using plastic bags.